The role of vitamin E succinate in regulation of growth and cyclooxygenase expression in B16 murine melanoma cells - Van der Merwe, Adele Shanette (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1999)
This study was undertaken to determine the effects and possible mechanism of action of vitamin E succinate supplementation on B16 murine melanoma cell growth in vitro. Studies revealed that supplementation of 5, 7 and 10Âµg/ml of this vitamin significantly inhibited growth of B16 cells. Non-malignant LLCMK cells supplemented with the same concentrations of vitamin E succinate resulted in similar inhibition of cell growth. The actual mechanism by which vitamin E succinate inhibits B16 cell growth is unclear, though there has been much speculation about its possible role as an antioxidant. Vitamin E succinate is not a physiological antioxidant and for this ester to behave as an antioxidant, cleavage of the ester bond must occur, releasing the antioxidant vitamin E part of the molecule. To determine whether the observed inhibitory effects on B16 cell growth were due to the intact vitamin E succinate or the vitamin E cleavage product, cleavage studies were undertaken. Results from these studies revealed that in B16 cells vitamin E succinate cleavage did not occur suggesting that the observed inhibitory effects of vitamin E succinate on B16 cells were due to the intact compound. In contrast vitamin E succinate cleavage was shown to occur in LLCMK cells, suggesting that these cells may contain an esterase capable of liberating succinic acid and vitamin E. Further studies focussed on the possible role of vitamin E succinate in regulation of cyclooxygenase activity in B16 cells as vitamin E succinate was found to effect the activity of various enzymes involved in the arachidonic acid cascade, notably cyclooxygenase, the rate-limiting enzyme in prostaglandin synthesis. Time course studies were used to determine when the cyclooxygenase protein was being produced, thus allowing an estimation of when the gene was being 'switched on'. These studies revealed that vitamin E succinate does not significantly effect cyclooxygenase activity in B16 cells over a period of 2 to 12 hours as compared to the OE control cultures. Further studies using RNA techniques investigated whether vitamin E succinate was having an effect on cyclooxygenase activity at a molecular level. These investigations were unsuccessful for the 6 day supplementation for a number of possible reasons, the main reason being RNA stability. Subsequent studies revealed an increase in COX mRNA after 2 hours, suggesting that the gene was 'switched on' soon after supplementation with vitamin E succinate, and further increases in COX mRNA were observed after 8 to 12 hours. The molecular studies were, however, inconclusive. Previous studies suggested that vitamin E succinate was indirectly causing growth inhibition of B16 cells via regulation of cyclooxygenase activity, however, this study does not support these findings and it would seem unlikely that regulation of cyclooxygenase expression in B16 cells by vitamin E succinate has a role to play in the mechanism by which vitamin E succinate inhibits growth in B16 cells.
Keywords: Melanoma; Vitamin E